The study of the awareness and participation of pharmacists in the “Affordable Medicines” government program - Huz, V. S. (Social Pharmacy in Health Care, 2023)
Aim. To study the awareness of pharmacists and their participation in the implementation of the “Affordable Medicines” government program when dispensing medicines for the treatment of arterial hypertension (AH); to determine directions for optimization of pharmaceutical care for dispensing medicines using electronic prescriptions (e-prescriptions) and improvement of training programs, thematic postgraduate cycles for pharmacists. Materials and methods. The objects of analysis were 291 questionnaires on information support for pharmacists regarding dispensing of medicines for patients with AH during the implementation of the “Affordable Medicines” program. The questionnaires were filled out by pharmacists from 8 regions of Ukraine, they were studying at specialization courses, thematic postgraduate cycles in the period from December 2021 to December 2022. Such methods as questionnaires, Google-forms, generalization, content analysis were used. Results. The analysis of the questionnaires showed that the largest percentage was pharmacists in the specialty “Organization and Management of Pharmacy”, who had more than 10 years of work experience. Among the surveyed pharmacists, 80 % work in pharmacies located in cities, which indicates an insufficient number of pharmacies and the implementation of the “Affordable Medicines” program in rural areas. According to the expert assessment, the following medicines are in the highest demand among hypertension patients using e-prescriptions: bisoprolol, enalapril, and clopidogrel, which are highly effective for the treatment of AH. It has been found that pharmacists consider it expedient to include new combined medicines and modern mono-preparations (perindopril, lisinopril, valsartan) in the Register; they are in demand among patients with AH at their own expense. It has been found that 96.3 % of pharmacists believe that it is necessary to receive more information support during the internship and thematic cycles on the pharmaceutical care for patients with AH according to evidence-based medicine, dispensing medicines according to e-prescriptions in the “Affordable Medicines” program in Ukraine. Conclusions. The results of the expert assessment of pharmacists indicate that dispensing of medicines by e-prescriptions for patients with AH in the “Affordable Medicines” program has significantly improved the economic availability of medicines for outpatient treatment. It has been determined that it is advisable to expand this program with combined medicines and mono-preparations, which are in demand among patients at their own expense. The expediency of postgraduate educational programs has been substantiated, and methodical support has been prepared for thematic cycles, trainings on pharmaceutical care and e-prescriptions for AH.